2007
DOI: 10.1021/jo070956t
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigating the Role of Multiple Hydrogen Transfers in Baeyer−Villiger Reactions

Abstract: A comparison between a tetramolecular mechanism (J. Org. Chem. 2007, 72, 3031) and our previously proposed mechanism has been performed. The results show that the tetramolecular mechanism is less favored in terms of Gibbs free energy, and therefore, the reaction in acidic media is acid catalyzed. The role of the catalyst in the migration step has been corrected and discussed. A new transition state is proposed for this step. The change in the rate-determining step for the cyclohexanone + performic acid reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 23 publications
3
49
0
Order By: Relevance
“…This reaction pathway is consistent with the kinetic results and the mechanistic proposal by List and Müller, [46] and it is similar to the mechanism of carboxylic acid catalyzed B-V oxidation using peracids proposed by Alvarez-Idaboy and co-workers. [19,22,23] Rationalization of the reactivities of different ketones towards the B-V reaction: The B-V reactions of acetone, cyclopentanone, and cyclohexanone were also examined theoretically, promoted by 1 c and using hydrogen peroxide as the oxidant. Because both the electrophilicity and hydrogen-bonding capability of these ketones can be expected to be similar to those of cyclobutanone, similar reactivity for the addition was assumed for both cyclic and acyclic ketones.…”
Section: The Phosphoric Acid Bound Criegee Intermediate (Int)mentioning
confidence: 99%
See 3 more Smart Citations
“…This reaction pathway is consistent with the kinetic results and the mechanistic proposal by List and Müller, [46] and it is similar to the mechanism of carboxylic acid catalyzed B-V oxidation using peracids proposed by Alvarez-Idaboy and co-workers. [19,22,23] Rationalization of the reactivities of different ketones towards the B-V reaction: The B-V reactions of acetone, cyclopentanone, and cyclohexanone were also examined theoretically, promoted by 1 c and using hydrogen peroxide as the oxidant. Because both the electrophilicity and hydrogen-bonding capability of these ketones can be expected to be similar to those of cyclobutanone, similar reactivity for the addition was assumed for both cyclic and acyclic ketones.…”
Section: The Phosphoric Acid Bound Criegee Intermediate (Int)mentioning
confidence: 99%
“…Most of these studies have investigated B-V reactions with peroxycarboxylic acids as oxidants. [17][18][19][20][21][22][23] Remarkably, even though calculations indicated that the reactions can be catalyzed by general acid catalysis, through hydrogen-bond formation, there are still some contradictory results in the mechanism elucidation with regards to the molecularity and the mode of activation. [21,23] For the mechanism elucidation of the B-V oxidation with hydrogen peroxide, only a few computational studies have been published.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, both theoretical and experimental investigations proved that BV oxidation reactions could be accelerated in the presence of acids. The acid molecule was assumed to act as both proton donor and acceptor, decreasing the activation barrier of the addition step 13a,e,f,i,j. Meanwhile, our experiments also indicated that the BV oxidation reaction between 1 a and m ‐CPBA could occur even without the Sc III – N , N ′‐dioxide complex, affording racemic products in a yield of 19 % 19.…”
Section: Resultsmentioning
confidence: 64%